A Unifying Approach for Investigating and Understanding Youth's Help and Care for the Family. (17th July 2019) - Armstrong‐Carter, Emma; Olson, Elizabeth; Telzer, Eva
Abstract: Youth provide significant contributions to their families, ranging from completing household chores to taking care of members of the family. Researchers have examined correlates, predictors, and consequences of the variation in youth's contributions to their families. One body of work has examined family assistance —youth's help with household chores. Another has looked at youth caregivers who provide significant, ongoing care to family members with health needs. This research has been disaggregated across various theoretical models, methods, and terms, making it difficult to investigate and understand the full spectrum of youth's contributions to the family. In this article, we summarize evidence about youth's help and care for the family across a fuller spectrum of behaviors and intensity, and review the challenges and strengths of myriad methods and conceptual models. We propose a unifying approach for investigating youth's contributions to the family that capitalizes on the strengths of each discipline and prioritizes interdisciplinary sharing of resources.